EFEKTIVITAS MODEL NHT MENGGUNAKAN MEDIA LAGU RUMUS MATEMATIKA TERHADAP HASIL BELAJAR MATEMATIKA SD - Apriliani, Yunisatizzahroh; Sutriyani, Wulan (Universitas Muhammadiyah Metro, 2024)
This research aims to determine the effectiveness of the NHT model on the mathematics learning outcomes of fifth grade elementary school students and wants to know their learning outcomes before and after using the NHT model. A one-group pretest-posttest experimental design is a part of this quantitative research approach. Thirty students were the sample for this research. The results of the t test indicate that H0 is rejected and Ha is accepted with a p-value of 0.000. With a Tcount of 11.498 and a Ttable of 2.048, we can see that the learning results for students were significantly different before and after using the NHT learning model. We reject H0 and accept Ha because Tcount > Ttable = 11.498 > 2.048. Consequently, the impact of the NHT learning model on the mathematics learning outcomes of fifth grade students at SD Negeri 3 Menganti is significantly different from other approaches.